Tourism and productivity: Case study of the hotel and catering industry in the Andalusian region - Eva Isabel González Guerrero; José López-Rubio (European Regional Science Association (ERSA), 2003)
The object of this paper is to analyse the situation and evolution of the productivity of the tourism industry in the Andalusian region, and more specifically of the hotel and catering branch, relating it to the organisational structure of its businesses. First of all, the issue of the definition and limitation of the concept of productivity applied to the services sector is addressed, as traditionally this concept is focused on manufacturing, and the different ways of measuring and the analysis methods are reviewed. Then, using the accounting information provided by the Balances Centre of Andalusia (CBA), the general features of the organisational structure of the hotel and catering industry in de Andalusian region, stratifying the samples by the size of the companies and examining the medium size of the Andalusian hotel and catering businesses. Once the organisational structure of the sector is analysed, it is related to the state and evolution of its productivity, using a simple ratio between the brute added value and the personnel expenses, and completing this analysis with a relative efficiency index, the Baldwin efficiency index, with which the technical efficiency of each company is compared to the mass of most efficient companies. As a result of this research it is observed that the productivity indexes increase as web as the size of the companies and during the considered period, especially in the case of the medium sized and large companies. Nevertheless, these productivity increases are less relevant than the increase of employment, especially in case of smaller companies.
Keywords: 330